Cutaneous Horn on the Right Supraclavicular Region in an Adolescent Female, a Rare Case Report - Gupta, Rohit; Kumar, Manoj; Sinha, Ruchi; Sahu, Reva Shankar (UI Scholars Hub, 2021)
Cutaneous horn (CH) is an outgrowth from the skin surface, composed of keratin, and associated with benign to malignant skin lesions. We report a case of CH in a 15-year-old female associated with Keratoacanthoma. It is uncommon in young people and is associated with a good prognosis because of its benign nature. This case needs to be reported as it highlights the rare occurrence of this condition in the younger age group and its good prognosis. Surgical excision is the treatment of choice, with histopathologic diagnosis playing a critical role in determining the nature and further treatment of this condition if required.